AS LIGAÇÕES QUÍMICAS PROPOSTAS POR LEWIS: UMA PERSPECTIVA EPISTEMOLÓGICA SOBRE A NATUREZA DESTE CONCEITO - Vitória S. da Silva; Fernanda K. D. da Silva; Jamily da S. dos Anjos; Alessandro Cury Soares; Bruno dos S. Pastoriza (Química Nova)
The study problematizes choices and traditional organizations of the chemical content in chemistry classes. The problematization is developed through an epistemological perspective, situated in the field of Chemistry Education, focusing on the construction of the concept of Chemical Bonds. It includes discussions in the fields of history and epistemology, but mainly presents the conceptions that preceded the nature of the Chemical Bonds concept proposed by Gilbert Newton Lewis, aiding in the understanding of its nature. This facilitates the creation of strategies and methodological practices that contribute to the teaching and learning process. We conclude that this study has enabled us to construct a pathway to understand the existing knowledge of that time and what contributed to Lewis’ proposal becoming the accepted theory by the scientific community of the time, persisting in Chemistry classes to this day.